2006
DOI: 10.1016/j.jvs.2006.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Population-based study of event-rate, incidence, case fatality, and mortality for all acute vascular events in all arterial territories (Oxford Vascular Study)

Abstract: Conclusion:Patients with thrombophilic abnormalities and venous thromboembolism (VTE) have an increased risk of recurrence of VTE.Summary: The authors studied the recurrence of VTE in patients with and without thrombophilic abnormalities who were treated with a standardized anticoagulation program. The analysis was from a prospective, multicenter, randomized study evaluating clinical benefit of 1 year of oral anticoagulant treatment vs a 3-month period of oral anticoagulant treatment after a first episode of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
274
3
23

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(310 citation statements)
references
References 0 publications
10
274
3
23
Order By: Relevance
“…The Atherosclerosis Risk in Communities Study reported a modest association between baseline depressive symptoms and incident PAD [46]. However, CVD and PAD have a common underlying arterial pathology and shared risk factors and epidemiology [47], and PAD predicts future stroke as well as events in other vascular territories [48]. Thus, whilst the direction of our cross-sectional association between PAD and depression is unknown, the presence of PAD could denote cerebrovascular risk in these patients.…”
Section: Discussionmentioning
confidence: 84%
“…The Atherosclerosis Risk in Communities Study reported a modest association between baseline depressive symptoms and incident PAD [46]. However, CVD and PAD have a common underlying arterial pathology and shared risk factors and epidemiology [47], and PAD predicts future stroke as well as events in other vascular territories [48]. Thus, whilst the direction of our cross-sectional association between PAD and depression is unknown, the presence of PAD could denote cerebrovascular risk in these patients.…”
Section: Discussionmentioning
confidence: 84%
“…21,22 Elderly women (above age 85 years) were observed to have higher stroke incidence than that in men. [23][24][25] Our LTR estimates emphasized that the LTR remains a major threat and public health burden for Japan's aging society, especially for women.…”
Section: Discussionmentioning
confidence: 97%
“…L'âge est le plus puissant : ainsi, après 55 ans, le risque d'AVC double à chaque décennie [10]. Le sexe masculin n'apparaît pas comme un facteur majeur dans la survenue d'un AVC contrairement à la pathologie coronarienne mais les données sont divergentes.…”
Section: Facteurs De Risque Non Modifiablesunclassified